2019
DOI: 10.15420/aer.2019.8.3.g1
|View full text |Cite
|
Sign up to set email alerts
|

British Heart Rhythm Society Clinical Practice Guidelines on the Management of Patients Developing QT Prolongation on Antipsychotic Medication

Abstract: The British Heart Rhythm Society’s Clinical Practice Guidelines on the Management of Patients Developing QT Prolongation on Antipsychotic Medication are written for heart rhythm consultants, primary care physicians, specialist registrars, nurses and physiologists who may be requested to review ECGs or advise on cases where antipsychotic-induced QT prolongation is suspected or proven. The guidance is adapted from the latest Maudsley Prescribing Guidelines in Psychiatry, published in 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 40 publications
1
36
0
1
Order By: Relevance
“…TdP is known to be a predictor of sudden death especially in patients with cardiac disease. This is an entirely separate mechanism from the primary pharmacological actions of antipsychotic medication and therefore a risk of arrhythmia is entailed which is not associated with any clinical advantage (Nielsen et al, 2011) The QTc interval is considered to be prolonged if greater than 440 ms for men and 470 ms for women, and a QTc over 500 ms should provoke considerable concern and prompt immediate cardiac review (Lambiase et al, 2019). A prolonged QTc may be familial and, along with the other adverse outcomes mentioned above (TdP, VT, VF), it is increased in prevalence by factors such as electrolyte imbalance (especially low potassium), liver disease, anorexia, alcohol use, some central nervous system disorders, female sex and a wide variety of cardiovascular disorders.…”
Section: Mortality Cardiovascular Disease and Antipsychotic Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…TdP is known to be a predictor of sudden death especially in patients with cardiac disease. This is an entirely separate mechanism from the primary pharmacological actions of antipsychotic medication and therefore a risk of arrhythmia is entailed which is not associated with any clinical advantage (Nielsen et al, 2011) The QTc interval is considered to be prolonged if greater than 440 ms for men and 470 ms for women, and a QTc over 500 ms should provoke considerable concern and prompt immediate cardiac review (Lambiase et al, 2019). A prolonged QTc may be familial and, along with the other adverse outcomes mentioned above (TdP, VT, VF), it is increased in prevalence by factors such as electrolyte imbalance (especially low potassium), liver disease, anorexia, alcohol use, some central nervous system disorders, female sex and a wide variety of cardiovascular disorders.…”
Section: Mortality Cardiovascular Disease and Antipsychotic Treatmentmentioning
confidence: 99%
“…Thioridazine and intravenous haloperidol remain the agents most associated with QTc prolongation and risk, although the latter’s risk is confounded by its use in very ill patients. Pimozide, sertindole, amisulpride and ziprasidone also appear to be among the antipsychotic medications most likely to prolong the QTc interval (Huhn et al, 2019; Lambiase et al, 2019).…”
Section: Mortality Cardiovascular Disease and Antipsychotic Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The dose used in our study was moderate, which has been shown to significantly increase the risk of cardiac death 14 . Guidelines recommend decreasing the dose or switching to safer alternatives when QTc is > 440 ms in males and > 470 ms in females, and stopping the drug when > 500 ms 24 .…”
Section: Discussionmentioning
confidence: 99%
“…In fact, a study showed that despite the prolongation in QT interval with atypical antipsychotics, there was no increased risk of torsades de pointes 23 . Nonetheless, olanzapine has a low risk of QT prolongation 24 , and the risk increases with dose 14 . The dose used in our study was moderate, which has been shown to significantly increase the risk www.nature.com/scientificreports/ of cardiac death 14 .…”
Section: Discussionmentioning
confidence: 99%